Phytochemical and Preliminary Pharmacological Evaluation of Diospyros blancoi Fruits - Das, Sreedam Chandra; Hossain, Md Sabbir; Tabassum, Nazifa; Rahman, Mohammad Sharifur; Bachar, Sitesh Chandra; Islam, Md Saiful (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Diospyros blancoi, a member of the Ebenaceae family known as ‘Bilati gab’ in Bangla, is traditionally used in treating a number of diseases. The study was aimed to isolate secondary metabolites from the fruits of D. blancoi and exploring the various pharmacological activities of the methanolic extract and its petroleum ether, chloroform and carbon tetrachloride fractions. Three compounds were obtained through phytochemical examination and identified as stigmasterol (1), lupeol (2) and betulinic acid (3) from the petroleum ether soluble fraction. In the castor oil-induced diarrhea model, methanolic extract and the petroleum ether fraction exhibited potent antidiarrheal activity with 42.04% (p < 0.001) and 36.94% (p < 0.001) defecation inhibition, respectively. The petroleum ether and carbon tetrachloride fraction showed mild to moderate efficacy in the hypoglycemic activity assay. In the tail flicking analgesic assay, methanol extracts and other fractions showed considerable central analgesic activity. In the acetic acid-induced writhing model, the petroleum ether fraction produced maximal (p < 0.001) peripheral analgesic properties. It is apparent from this study that D. blancoi fruits serve as a reservoir of potential bioactive molecules that might have novel analgesic or antidiarrheal activities, and further considerable investigations to find possible lead candidates are suggestive of this study. Dhaka Univ. J. Pharm. Sci, 23(2): 113-122, 2024 (December)